Manajemen Fraud di Bank Syariah: Studi Kualitatif tentang Pencegahan dan Penanganan Kecurangan: Indonesia - Irvan Dian Budiarto (Cashless : Journal of Sharia Finance and Banking, 2023)
Islamic banking has experienced rapid growth in recent decades, but it still faces major challenges in preventing and handling fraud. Fraud not only threatens the financial stability of Islamic banks, but can also damage public trust in the sharia principles that are the basis for their operations. This study aims to analyze fraud management in Islamic banks with a qualitative approach, especially in prevention strategies and handling mechanisms. The results of the study show that fraud prevention strategies in Islamic banks involve strengthening the internal control system, sharia audits, and increasing the role of Sharia Compliance Officers and Internal Auditors. In addition, education and training for employees and customers is an important step in building an anti-fraud culture. In terms of handling fraud, Islamic banks must implement transparent and accurate investigations, as well as coordinate with the Financial Services Authority (OJK), Bank Indonesia (BI), and the Sharia Supervisory Board (DPS) to ensure compliance with sharia regulations and principles. This study emphasizes that the implementation of good corporate governance, strong internal control, and compliance with sharia principles are the main factors in preventing and handling fraud in Islamic banks. With a comprehensive strategy and based on Islamic values, Islamic banks can increase transparency, accountability, and public trust in the Islamic banking system. Keyword : Fraud Management, Sharia Banks, Fraud Prevention, Sharia Audit, Good Corporate Governance, Sharia Compliance